Phytochemistry, Biological Activities, and Chemical Profiling of Berberis asiatica - Bhattarai, Keshab; Dhakal, Devendra; Pandey, Indira; Subba, Bimala; Sharma, Khaga Raj (BIBECHANA, 2023)
This study focused on chemical profiling and assessed the total phenolic and flavonoid content as well as the antioxidant and antibacterial effect of the medicinal plant Berberis asiatica. The results revealed that this plant has high concentrations of TPC (Total phenol content) and TFC (Total flavonoid content) of 37.686 ± 2.728 mg GAE/g and 115.568 ± 8.012 mg QE/g, respectively. The DPPH free radical scavenging assay demonstrated strong inhibition, with an IC50 of 205.7 ± 5.353 μg/mL, and also showed robust antibacterial properties against Staphylococcus aureus and Klebsiella pneumoniae with a zone of inhibition (ZOI) of 14 mm and 19 mm, respectively. The extract exhibited an excellent inhibitory potential against S. aureus, and K. pneumoniae with an MIC (Minimum inhibitory concentration) of 0.39 mg/mL, and 3.125 mg/mL respectively, indicating significant inhibitory action. Furthermore, the MBC (Minimum bactericidal concentration) for both S. aureus and K. pneumoniae was found to be 6.25 mg/mL, emphasizing the extract's consistent bactericidal effectiveness against these bacteria. These findings underscore the potential utility of the methanolic extract of Berberis asiatica as a natural antibacterial agent. GC-MS analysis of hexane fraction indicates the plant is rich in secondary metabolites, specifically 2,2-dimethyl-3-pentanol, 2-methyl-2-pentanol, 2,5-dimethyl-4-hydroxy-3-hexanone, 3-hexanol, 4-methyl-2-pentanol are identified. Overall, this study highlights the importance of plant-based natural products as potential sources of antioxidants and antibacterial agents that contributes to the future drug development process.